2013
DOI: 10.1021/jo402149f
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomerization inN-aryl-2(1H)-pyrimidin-(thi)ones: A Ring-Opening/Rotation/Ring-Closure Process in Place of a Classical Rotation around the Pivot Bond

Abstract: Uncatalyzed racemization processes in atropisomeric diphenyl-like frameworks are classically described as the result of the rotation around the pivotal single bond linking two planar frameworks. Severe constraints leading to more or less distorted transition states account for the experimental barrier to atropenantiomerization. In 1988, one of us hypothesized that, in N-aryl-2(1H)-pyrimidin-(thi)ones, a ring-opening/ring-closure process was contributing to the observed racemization process accounting for the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…It is also a major aspect to consider in medicinal chemistry to rationalize biological or enzymatic activities and in synthesis to explain reactivity and stereochemistry or to propose mechanisms . Furthermore, careful attention must be paid to steric parameters during investigations on nanomaterials and in dynamic stereochemistry …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a major aspect to consider in medicinal chemistry to rationalize biological or enzymatic activities and in synthesis to explain reactivity and stereochemistry or to propose mechanisms . Furthermore, careful attention must be paid to steric parameters during investigations on nanomaterials and in dynamic stereochemistry …”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, careful attention must be paid to steric parameters during investigations on nanomaterials 10 and in dynamic stereochemistry. 11 Therefore, ranking molecular fragments according to their apparent size represents a crucial point of interest. Measurements of steric bulk such as the Taft E s values were first derived from kinetic data 12 and considerable efforts were devoted to the separation of electronic from purely steric contributions in these models.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, this compound racemizes swiftly in apolar solvents at elevated temperatures ( t 1/2 = 4 min in xylene at 50 °C), whereas racemization at room temperature in polar solvents is negligible. 11 Racemization takes place relatively easily since it proceeds via a reversible ring-opening and closing-mechanism, 12 rather than via rotation around the chiral axis. Fujita and co-workers already showed that total spontaneous resolution can be achieved for this compound.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the concerned binding breaks go through a sort of SMILES transformations with a lower energy, following the principle of favoring the longest chain in molecular configuration. This is already a sort of structural variational principle in chemical bonding [ 108 ]; By the recent QSARINS-Chem model for QSAR studies recognizing the role of SMILES canonical rules in correctly assessing the query and parsing the structure-activity algorithm (for the LoSMoC and BraS conformations, for instance) [ 109 ]. …”
Section: Smiles Of Anti-hiv Pyrimidinesmentioning
confidence: 99%
“…Therefore the concerned binding breaks go through a sort of SMILES transformations with a lower energy, following the principle of favoring the longest chain in molecular configuration. This is already a sort of structural variational principle in chemical bonding [ 108 ];…”
Section: Smiles Of Anti-hiv Pyrimidinesmentioning
confidence: 99%